Association of Obesity with Forearm Fractures, Bone Mineral Density and Fracture Risk (FRAX®) During Postmenopausal Period - Erkan Mesci; Nilgün Mesci; Afitap İçağasıoğlu; Ercan Madenci (Türk Osteoporoz Dergisi, 2016)
Objective: The aim of this study was to investigate the association among obesity with bone mineral density (BMD) and subsequent fracture risk among postmenopausal women with a previous forearm fracture. Materials and Methods: The study enrolled obese (n=40) and normal-weight (n=40) postmenopausal women who had a previous forearm fracture. BMD measurements were obtained using a GE-LUNAR DPX dual energy X-ray absorptiometry scan for all subjects. FRAX® fracture risk scores were calculated taking into account former fractures and current risk factors of the subjects. Both groups were compared with respect to their BMD values, T scores, FRAX® risk scores and frequency of previous fractures. Results: No difference was observed between groups with regard to mean age, mean age of menopause onset and mean serum calcium, phosphorus and alkaline phosphatase levels (p>0.05 for all). Statistically, obese patients showed highly significantly greater mean BMD values at lumbar spine (L1-L4) and femoral neck in comparison to subjects with normal body weight (p=0.000 for all). Obese patients had a lower 10-year probability of a major osteoporotic fracture on average as determined by FRAX® fracture risk score compared to that in normal-weight subjects (p<0.05). Also, obese group had a lower 10-year probability of a hip fracture versus normal-weight subjects (p<0.01). Both groups were found to have a similar frequency of previous fractures. Conclusion: Although obese patients in this study had greater BMD values and lower FRAX® risk scores, the probability of subsequent fractures predicted for the obese group was not lower when compared to that predicted for normal-weight group. It should be kept in mind that obesity may not necessarily be protective against fractures and treatment algorithms based solely on BMD might be inadequate to predict future fracture risk.